Resisting Invasions: Indigenous Peoples and Land Rights Battles in Mabo and Terra Vermelha - Aline Frey (Ilha do Desterro)
This article examines two feature films, focusing on the link between Indigenous cinema, environmental preservation and land rights. The first film is Mabo (2012) directed by Aboriginal filmmaker Rachel Perkins. It centres on a man’ legal battle for recognition of Indigenous land’ ownership in Australia. The second film is Terra Vermelha (Birdwatchers, Marco Bechis, 2008), which centres on the violence endured by a contemporary Brazilian Indigenous group attempting to reclaim their traditional lands occupied by agribusiness barons. Based on comparative analysis of Mabo and Terra Vermelha, this article discusses the similar challenges faced by Indigenous nations in these two countries, especially the colonial dispossession of their ancestral territories and the postcolonial obstacles to reclaim and exercise self-determination over them.